Gut microbiota–derived metabolites and risk of coronary artery disease: a prospective study among US men and women. Issue 1 (7th April 2021) - Liu, Gang; Li, Jun; Li, Yanping; Hu, Yang; Franke, Adrian A; Liang, Liming; Hu, Frank B; Chan, Andrew T; Mukamal, Kenneth J; Rimm, Eric B; Sun, Qi
ABSTRACT: Background: Accumulating evidence has suggested that human gut microbiota metabolize certain dietary compounds and subsequently produce bioactive metabolites that may exert beneficial or harmful effects on coronary artery disease (CAD) risk. Objectives: This study examined the joint association of 2 gut microbiota metabolites, enterolactone and trimethylamine N-oxide (TMAO), that originate from intake of plant-based foods and animal products, respectively, in relation to CAD risk. Methods: A prospective nested case—control study of CAD was conducted among participants who were free of diabetes, cardiovascular disease, and cancer in the Nurses' Health Study II and the Health Professionals Follow-up Study. Plasma concentrations of enterolactone and TMAO, as well as choline and L-carnitine, were assayed among 608 CAD case-control pairs. Results: A high enterolactone and low TMAO profile was associated with better diet quality, especially higher intake of whole grains and fiber and lower intake of red meats, as well as lower concentrations of plasma triglycerides and C-reactive protein. Participants with a high enterolactone/low TMAO profile had a significantly lower risk of CAD: the multivariate-adjusted OR was 0.58 (95% CI: 0.38, 0.90), compared with participants with a low enterolactone/high TMAO profile. No significant interaction between enterolactone and TMAO on CAD risk was observed. Neither TMAO nor enterolactone alone were associated with CAD risk in pooled analyses. In women, a higher enterolactone concentration was significantly associated with a 54% lower CAD risk ( P trend = 0.03), although the interaction by sex was not significant. Conclusions: Our results show that a profile characterized by high enterolactone and low TMAO concentrations in plasma is linked to a healthful dietary pattern and significantly associated with a lower risk of CAD. Overall, these data suggest that, compared with individual markers, multiple microbiota-derived metabolites may facilitate better differentiation of CAD risk and characterization of the relations between diet, microbiota, and CAD risk.